2022
DOI: 10.1096/fj.202200455rrr
|View full text |Cite
|
Sign up to set email alerts
|

Retinal degeneration induced in a mouse model of ischemia–reperfusion injury and its management by pemafibrate treatment

Abstract: Retinal ischemia-reperfusion (I/R) injury is a common cause of visual impairment. To date, no effective treatment is available for retinal I/R injury. In addition, the precise pathological mechanisms still need to be established. Recently, pemafibrate, a peroxisome proliferator-activated receptor α (PPARα) modulator, was shown to be a promising drug for retinal ischemia. However, the role of pemafibrate in preventing retinal I/R injury has not been documented. Here, we investigated how retinal degeneration occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 117 publications
(299 reference statements)
0
11
0
Order By: Relevance
“…Previously, we found pathologic increases in isolectin GS-IB4 (IB4)-positive inflammatory cells in the retina five days after retinal I/R injury [ 13 ]. Therefore, we examined whether the likelihood of its occurrence could be lessened by NMN treatment ( Figure 2 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we found pathologic increases in isolectin GS-IB4 (IB4)-positive inflammatory cells in the retina five days after retinal I/R injury [ 13 ]. Therefore, we examined whether the likelihood of its occurrence could be lessened by NMN treatment ( Figure 2 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports from us and others have suggested that reductions in pathologic retinal inflammatory cells could be beneficial for retinal neuronal protection in a murine model of retinal I/R injury [ 13 , 32 , 33 ]. The therapeutic strategy of modulating pathologic inflammatory cells for neuroprotection can be seen in brain injury, rather than just retinal I/R injury [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations